Characteristics of Carotid Artery Structure and Mechanical Function and Their Relationships with Aortopathy in Patients with Bicuspid Aortic Valves - Kim, Mihyun; Shim, Chi Young; You, Seong-Chan; Cho, In-Jeong; Hong, Geu-Ru; Ha, Jong-Won; Chung, Namsik (Frontiers in Physiology, 2017)
Patients with a bicuspid aortic valve (BAV) often have proximal aortic dilatation and systemic vascular dysfunction. We hypothesized that BAV patients would have different carotid artery structural and functional characteristics compared to tricuspid aortic valve (TAV) patients. In 28 patients with surgically confirmed BAV and 27 patients with TAV, intima media thickness (IMT), number of plaques, fractional area change (FAC), global circumferential strain (GCS), and standard deviation of CS (SD-CS) in both common carotid arteries were assessed using duplex ultrasound and velocity vector imaging (VVI). Patients with BAV were younger and had less co-morbidity, but showed a significantly larger ascending aorta (43.3±7.5 vs. 37.0±6.2 mm, p<0.001) and a higher prevalence of aortopathy (61 vs. 30%, p=0.021) than those with TAV. BAV patients showed a significantly lower IMT and fewer plaques. Although FAC and GCS were not significantly different between the two groups, they tended to be lower in the BAV group when each group was divided into three subgroups according to age. There was a significant age-dependent increase in IMT and decreases in FAC and GCS in the TAV group (p=0.005, p=0.001, p=0.002, respectively), but this phenomenon was not evident in the BAV group (p=0.074, p=0.248, p=0.394, respectively). BAV patients with aortopathy showed a higher SD-CS than those without aortopathy (p=0.040), reflecting disordered mechanical function. In conclusion, BAV patients have different carotid artery structure and function compared with TAV patients, suggesting intrinsic vascular abnormalities that are less affected by established cardiovascular risk factors and more strongly related to the presence of aortopathy.